Ahluwalia, Isher Judge, Industrial Growth in India Stagnation since the Mid-Sixties, Oxford University Press, Delhi-Bombay-Calcutta-Madras, 1985, xxiv + 235 pp. - Wionczek, Miguel S. (Estudios de Asia y África, 1985)
-